ANALISIS TINGKAT KEPERCAYAAN DIRI ATLET ANGKAT BESI PABSI JAMBI - Desi Fitriani; David Iqroni; Ceppy Pradana Putra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Athletes with a good level of self-confidence tend to be able to control anxiety, cope with competitive pressure, and maintain consistent performance during training and matches. However, based on field observations, there are still athletes who show doubts about their abilities, especially when facing opponents with higher achievements. This study aims to determine and analyze the level of self-confidence of PABSI Jambi weightlifters. This study uses a quantitative descriptive approach. The subjects of the study were 15 PABSI Jambi weightlifters who actively participate in the training program. The instrument used was a self-confidence questionnaire with a Likert Scale that has been tested for validity and reliability, with a Cronbach's Alpha value of 0.861 indicating a high level of reliability. Data were analyzed using descriptive statistics by calculating the minimum, maximum, mean, standard deviation, and category distribution values ​​with the help of SPSS version 27. The results showed that the level of self-confidence of PABSI Jambi weightlifters was in the high category with an average value of 66.60. The data distribution shows that 2 respondents (13.3%) were in the very low category, 2 respondents (13.3%), 3 respondents (20.0%) were in the moderate category, 5 respondents (33.3%) were in the high category, and 3 respondents (20.0%) were in the very high category. These findings indicate that most athletes have a good level of self-confidence to support their athletic performance. Based on these results, it can be concluded that the general level of self-confidence of PABSI Jambi weightlifters is in the high category. However, some athletes still have low levels of self-confidence who require attention in mental development to improve psychological readiness and optimal competitive performance.